Comparing absolute and normalized indicators in scientific collaboration: a study in Environmental Science in Latin America - Cabrini Gracio, Maria Claudia [UNESP]; Tannuri de Oliveira, Ely Francina [UNESP]; Rafols, I; MolasGallart, J.; CastroMartinez, E.; Woolley, R. (Univ Politecnica Valencia, 2016)
This paper aims to conduct a comparative analysis of scientific collaboration proximity trends generated from absolute indicators and indicators of collaboration intensity in the field of Environmental Sciences in Latin America (LA), in order to identify possible existing biases in the absolute indicators of international cooperation, due to the magnitude of scientific production of these countries in mainstream science. More specifically, the objective is to analyze the compared forms of absolute and normalized values of co-authorship among Latin America countries and their main collaborators, in order to observe similarities and differences expressed by two indexes of frequency in relation to scientific collaboration trends in LA countries. In addition, we aim to visualize and analyze scientific collaboration networks with absolute and normalized indexes of co-authorship through SC among Latin America countries and their collaborators, comparing proximity evidenced by two generated collaborative networks - absolute and relative indicators. Data collection comprised a period of 10 years (2006-2015) for the countries from LA: Brazil, Mexico, Argentina, Chile and Colombia as they produced 94% of total production, a percentage considered representative and significant for this study. Then, we verified the co-authorship frequencies among the five countries and their key collaborators and builted the matrix with the indexes of co-authorship normalized through SC. Then, we generated two egocentric networks of scientific collaboration -absolute frequencies and normalized frequencies through SC using Pajek software. From the results, we observed the need for absolute and normalized indicators to describe the scientific collaboration phenomenon in a more thoroughly way, once these indicators provide complementary information.